Modeling dysbiosis of human NASH in mice: Loss of gut microbiome diversity and overgrowth of Erysipelotrichales. - James K Carter (Public Library of Science (PLoS), 2021)
Background & aim Non-alcoholic steatohepatitis (NASH) is a severe form of non-alcoholic fatty liver disease (NAFLD) that is responsible for a growing fraction of cirrhosis and liver cancer cases worldwide. Changes in the gut microbiome have been implicated in NASH pathogenesis, but the lack of suitable murine models has been a barrier to progress. We have therefore characterized the microbiome in a well-validated murine NASH model to establish its value in modeling human disease. Methods The composition of intestinal microbiota was monitored in mice on a 12- or 24-week NASH protocol consisting of high fat, high sugar Western Diet (WD) plus once weekly i.p injection of low-dose CCl4. Additional mice were subjected to WD-only or CCl4-only conditions to assess the independent effect of these variables on the microbiome. Results There was substantial remodeling of the intestinal microbiome in NASH mice, characterized by declines in both species diversity and bacterial abundance. Based on changes to beta diversity, microbiota from NASH mice clustered separately from controls in principal coordinate analyses. A comparison between WD-only and CCl4-only controls with the NASH model identified WD as the primary driver of early changes to the microbiome, resulting in loss of diversity within the 1st week. A NASH signature emerged progressively at weeks 6 and 12, including, most notably, a reproducible bloom of the Firmicute order Erysipelotrichales. Conclusions We have established a valuable model to study the role of gut microbes in NASH, enabling us to identify a new NASH gut microbiome signature.